PENGARUH BIMBINGAN ORANG TUA SINGLE PARENT TERHADAP MOTIVASI BELAJAR SISWA DI SMA NEGERI 1 SINGINGI HILIR DESA KOTO BARU KABUPATEN KUANTAN SINGINGI - Melinda, Vivin Septia; Hambali, Hambali; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the guidance of single parent parents on students' learning motivation at SMA Negeri 1 Singingi Hilir, Koto Baru Village, Kuantan Singingi Regency. The formulation of the problem in this study is how the influence of single parent parental guidance on student learning motivation in SMA Negeri 1 Koto Baru Village, Singingi Hilir District, Kuantan Singingi Regency. The purpose of the study was to determine the effect of single parent guidance on student learning motivation at SMA Negeri 1 Koto Baru Village, Singingi Subdistrict, Kuantan Singingi Regency. The benefits of this research are that the theoretical benefits of this research should be able to make a contribution to education, especially in tutoring and learning motivation. The population in this study were all students at SMA Negeri 1 Singingi Hilir, totaling 173 students. The sample in this study were students who lived with single parent parents, totaling 19 respondents who were determined by total sampling technique. Data collection instruments are questionnaires, documentation, and interviews. Data processing with quantitative descriptive analysis using a simple linear regression formula using the SPSS version 16.0 application by stating the hypothesis; there is an influence between tutoring on student motivation at SMA Negeri 1 Singingi Hilir. Based on the results of the study, there is a significant influence between single parent parenting tutoring on learning motivation. This is evidenced by the results of a simple linear regression test using SPSS version 16.0 where between variables X and Y is y = 0.795 + 0.788, from the results of the F test obtained Fcount, 28,011 and Ftable of (4.21) where it shows that Fcount > Ftable, Ho is rejected and Ha is accepted.Key Words: Influence, Tutoring, Student Learning Motivation.